Orbital Glial Heterotopia: A Report of 2 Cases and Review of the Literature. Issue 1 (January 2020) - Mehta, Neesurg S.; Tenzel, Phillip A.; Sharfi, Duaa; Colley, Patrick; Iacob, Codrin; Reddy, Harsha S.
Abstract : Purpose: To review the clinical radiographic and histopathologic findings associated with orbital glial heterotopia. Methods: A literature search in PubMed and Scopus was performed to include all articles published in English between 1980 and January 1, 2019. A case series including 29 case reports of 29 patients, as well as the authors' 2 cases, were considered in the literature review. Results: The majority of the cases had onset of symptoms (86%) and age at presentation (71%) before 5 years of age. The most common presenting symptoms and signs were swelling (45%), strabismus (32%), and proptosis (26%). The most common lesion locations described were inferolateral (19%) or primarily posterior orbital or apical (19%). The most common findings associated with orbital glial heterotopia were microphthalmia (10%) and anophthalmia (6%); however, the majority did not have systemic abnormalities (71%). The most common imaging modality was CT scan (71%). Diagnosis was made with histologic analysis in all cases, and confirmed after subtotal resection (35%), total resection (39%), or incisional biopsy (26%). The majority of the cases report no growth on repeat imaging, with only 3 reports of recurrence. Conclusions: Glial heterotopia in the orbit is a rare clinical entity most commonly presenting in children. We present 2 cases of orbital glial heterotopia in adults, with a literature on these lesions in both the pediatric and adult populations. Surgeons and pathologists should be aware of this atypical presentation in adulthood. Biopsy is required for diagnosis but is not without risk. Prognosis is generally favorable. Orbital glial heterotopia, commonly considered a rare congenital lesion generally presenting in children, may first become symptomatic in adulthood. Biopsy is required for diagnosis, with symptoms and prognosis dependent on location and growth of the lesion.